Therapeutic Mode of Action of Methotrexate - Byamba, Dashlkhumbe; Kim, Do-Young; Soodoi, Chimidtseren; Yadamsuren, Enkhtur; Munkhbayar, Ariunaa; Batbayar, Nandintsetseg; Dashdondov, Dashkhajidmaa; Batsaikhan, Oyuntsatsral; Gunchin, Batbaatar; Lee, Min-Geol (Central Asian Journal of Medical Sciences, 2016)
Objectives: Methotrexate (MTX) has been used in clinical practice for over a half-century and its action mechanism is believed to rely on the direct inhibition of DNA synthesis leading to suppression of cell proliferation. However, its anti-inflammatory action mechanism is not fully explained. In some autoimmune or overactive immune-related diseases such as psoriasis, it has been demonstrated that interleukin (IL)-23/IL-17/lL-22 pathway plays a key role in disease pathogenesis. In this study, we aimed to investigate the suppressive action of MTX on the IL[1]23/1 L-17/1 L-22 pathway in psoriasis. Methods: We made a model of psoriasis on mice using imiquimod (IMQ). The mice were divided into three groups: disease-free control group and disease-induced groups with no treatment and MTX-treatment. Clinical, histological and immunological parameters were evaluated among the groups. Results: Treatment with MTX decreased the psoriatic skin changes and the histological alterations induced by IMQ. MTX exerted its treatment effects via inhibition of the main players in the pathogenetic axis, the IL-23, IL-17A, F and IL-22, that were found to be increased in the diseased mice. Regulatory T cells expressing CTLA4 or GITR or PD1 molecules on their surface were not related to these decrements. Conclusion: The therapeutic action mechanism of MTX is related to the direct inhibition of the IL-23/1 L-17/1 L-22 pathway, but not the induction of inhibitory molecules or expansion of regulatory T cells.